EMAGINE–Study protocol of a randomized controlled trial for determining the efficacy of a frequency tuned electromagnetic field treatment in facilitating recovery within the subacute phase following ischemic stroke - Saver, Jeffrey L.; Duncan, Pamela W.; Stein, Joel; Cramer, Steven C.; Eng, Janice J.; Lifshitz, Assaf; Hochberg, Arielle; Bornstein, Natan M. (Frontiers in Neurology, 2023)
Stroke is a leading cause of disability with limited effective interventions that improve recovery in the subacute phase. This protocol aims to evaluate the safety and efficacy of a non-invasive, extremely low-frequency, low-intensity, frequency-tuned electromagnetic field treatment [Electromagnetic Network Targeting Field (ENTF) therapy] in reducing disability and promoting recovery in people with subacute ischemic stroke (IS) with moderate-severe disability and upper extremity (UE) motor impairment. Following a sample-size adaptive design with a single interim analysis, at least 150 and up to 344 participants will be recruited to detect a 0.5-point (with a minimum of 0.33 points) difference on the modified Rankin Scale (mRS) between groups with 80% power at a 5% significance level. This ElectroMAGnetic field Ischemic stroke–Novel subacutE treatment (EMAGINE) trial is a multicenter, double-blind, randomized, sham-controlled, parallel two-arm study to be conducted at approximately 20 United States sites, and enroll participants with subacute IS and moderate-severe disability with UE motor impairment. Participants will be assigned to active (ENTF) or sham treatment, initiated 4–21 days after stroke onset. The intervention, applied to the central nervous system, is designed for suitability in multiple clinical settings and at home. Primary endpoint is change in mRS score from baseline to 90 days post-stroke. Secondary endpoints: change from baseline to 90 days post-stroke on the Fugl-Meyer Assessment - UE (lead secondary endpoint), Box and Block Test, 10-Meter Walk, and others, to be analyzed in a hierarchical manner. EMAGINE will evaluate whether ENTF therapy is safe and effective at reducing disability following subacute IS. Trial registration www.ClinicalTrials.gov, NCT05044507 (14 September 2021).